JELAJAH STREET FOOD TANAMODINDI: PRODUK UNGGULAN DALAM PERSPEKTIF KONSUMEN - Nuraisyah Nuraisyah; Gita Farista; Agus Ardi; Asti Cintami Putri; Ivana Toheke; Mahwalda Septianingsih; Mega Triana Monduale (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Street food has become a phenomenal culinary in today's modern culinary scope. The research explores consumer perspectives in identifying superior products enjoyed at street food. This research applies a descriptive qualitative approach to find an overview of consumer perspectives on superior street food products. The findings of the study found that the superior product of street food indicates that the superior product produces four main points involving authentic flavors that need to be highlighted so as to build the soul of consumers in remembering and marketing by word of mouth, then affordable prices are the main points. Furthermore, kolabarosi is mixed and matched in today's culinary and modern culinary which ultimately encourages the entrepreneurial spirit of young people in developing their creativity through street food.